THE SUGGESTED VIDEO CONFERENCING APPLICATIONS FOR LANGUAGE LEARNING (Journal of Foreign Language Studies, 2024)
The article presents a general concept of distance training technology with ICT applications, summarizing some foreign language teaching-learning methods, technical factors affecting the implementation of a training program with ICT; the use of online videoconferencing to support language teaching and learning. At the same time, the article also suggests and introduces some popular videoconferencing programs, mostly free of charge, to be used in foreign language training institutions in Vietnam.